Staff reporting and staff development - Anstey, Edgar; Robertson, Andrew B. (London : Published for the Royal Institute of Public Administration by Allen & Unwin, 1961)
This book explains the objectives of staff assessment, methods of staff assessment that are based principally on annual or other periodic confidential reports, staff appraisal interviews, and description of a staff development scheme.
Includes bibliographical footnotes and index.
ne 12/07/2018
Loans
Keywords: Management